SEXUAL HEALTH BEHAVIORS OF ADOLESCENTS IN POKHARA, NEPAL - Niranjan, Shrestha; Damaru, Prasad Paneru; Kalpana, Jnawali (Indian Journal of Community Health, 2012)
BACKGROUND: Adolescent (10–19 years) is a transition of age during which hazardous sexual health behaviors may be adopted; increasing vulnerability to several kinds of behavioral disorders like drug use, unsafe sexual act leading to reproductive ill health. Objective of the study was to assess sexual health behaviors of adolescents in Pokhara, Nepal. METHODS: An institution based cross-sectional study was conducted among 15–19 years adolescents studying in grades 11 and 12. Probability sampling techniques were applied. A structured, pretested, envelope sealed self administered questionnaire was distributed among all (1584) adolescents of the 11 and 12 grades of selected institutions. Data were analyzed using Statistical Package for Social Sciences (16 versions). Descriptive and inferential statistics were applied. RESULTS: About 19.37% adolescents had sexual contact and male participation was higher than females (P<0.05). Nearly one fifth of unmarried were found to be involved in sexual activities and most of them had first sex between 15-19 years age (median age 15.26 years). Of those who had sex, 6.91% had adopted all the three: vaginal, oral and anal sexes and majority had single followed by 2-5 sex partners in their sexual intercourse in the last one year and last month. About 13.93% adolescents were found to be indulged in group sex. Most of them had sex with regular partners and commercial sex workers. More than eight out of every ten who had sex had used contraceptive methods and condom was method of choice (94.77%). CONCLUSIONS: Premarital sexual involvement was prevalent among adolescents; sex with commercial sex workers and non commercial sex partners was perceived to be risk. Behavior change intervention strategies need to be formulated and implemented to promote adolescent reproductive and sexual health.